2011
DOI: 10.1097/bsd.0b013e3181ddf124
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Seizure After Percutaneous Endoscopic Lumbar Discectomy

Abstract: Although rare (0.02%), seizure can occur in patients undergoing PELD, occurrence of neck pain is correlated with increase in cervical epidural pressure, which should be considered as prodromal sign and alert the surgeon. Duration of procedure and speed of infusion are associated risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 0 publications
1
49
0
2
Order By: Relevance
“…There several randomized controlled studies have demonstrated that the new method showed great effectiveness in the treatment of LDH which is consistent with our study [8,13,14]. While PTED brings great benefits to most patients, a small number of them have poor outcomes or complications [15,16]. Therefore, we need further research to explore the best indications for PTED so as to bring the greatest benefit to patients with LDH.…”
Section: Discussionsupporting
confidence: 87%
“…There several randomized controlled studies have demonstrated that the new method showed great effectiveness in the treatment of LDH which is consistent with our study [8,13,14]. While PTED brings great benefits to most patients, a small number of them have poor outcomes or complications [15,16]. Therefore, we need further research to explore the best indications for PTED so as to bring the greatest benefit to patients with LDH.…”
Section: Discussionsupporting
confidence: 87%
“…However, contraindications and inadequate indications have not been fully reported (19)(20)(21). In this study we showed that a narrow foramen (foraminal height ≥13 mm, foraminal width ≥7 mm) is not a limiting factor in PLA for PELD; however, we observed early recurrence in 1 patient who presented with local scoliosis (coronal Cobb angle =13°), and in 1 patient with suspected instability who showed no improvement in the NRS score.…”
Section: Discussionmentioning
confidence: 63%
“…Choi et al (15) reported 4 cases of seizure among 16.725 cases of PED. They complained neck pain before seasure ; thus, it must be the indicator of the consequent seizure.…”
Section: Discussionmentioning
confidence: 99%